Cost- utility analysis of cast compared to removable brace in the management of adult patients with ankle fractures. (2022) - Nwankwo, H.; Mason, J.; Costa, M. L.; Parsons, N.; Redmond, A.; Parsons, H.; Haque, A.; Kearney, R. S.
No abstract available